Is There an Obligation to Stay Young? The Progress of the Social Integration of Youths in Three African Capitals: Dakar, Yaounde, Antananarivo - (:unkn) unknown (My University, 2001)
Victims of the long crisis that has affected their countries, the youth of three African capitals (Dakar, Yaoudé and Antananarivo) find themselves forced to postpone agenda marking their entry into adult life. This postpones not only obtaining their first paid employment but also moving into their first home and founding a family. Neither their higher level of education, nor the delays in attaining adult status protect their future, nor prevent worsening living conditions compared to those of their parents’ generation at their coming of age. In fact, we are witnessing a situation where the higher the education level, the more these young people are disadvantaged by the deterioration of the economic environment.
Keywords: African Research